Enzymatic Crosslinked Hydrogels of Gelatin and Poly (Vinyl Alcohol) Loaded with Probiotic Bacteria as Oral Delivery System - Aldo F. Corona-Escalera; Ernesto Tinajero-Díaz; Rudy A. García-Reyes; Gabriel Luna-Bárcenas; Ali Seyfoddin; José Daniel Padilla-de la Rosa; Marisela González-Ávila; Zaira Y. García-Carvajal (MDPI AG, 2022)
Probiotic bacteria are widely used to prepare pharmaceutical products and functional foods because they promote and sustain health. Nonetheless, probiotic viability is prone to decrease under gastrointestinal conditions. In this investigation, Lactiplantibacillus plantarum spp. CM-CNRG TB98 was entrapped in a gelatin-poly (vinyl alcohol) (Gel-PVA) hydrogel which was prepared by a "green" route using microbial transglutaminase (mTGase), which acts as a crosslinking agent. The hydrogel was fully characterized and its ability to entrap and protect L. plantarum from the lyophilization process and under simulated gastric and intestine conditions was explored. The Gel-PVA hydrogel showed a high probiotic loading efficiency (>90%) and survivability from the lyophilization process (91%) of the total bacteria entrapped. Under gastric conditions, no disintegration of the hydrogel was observed, keeping L. plantarum protected with a survival rate of >94%. While in the intestinal fluid the hydrogel is completely dissolved, helping to release probiotics. A Gel-PVA hydrogel is suitable for a probiotic oral administration system due to its physicochemical properties, lack of cytotoxicity, and the protection it offers L. plantarum under gastric conditions.